External extreme wind pressure distribution for the structural design of cooling towers. (15th February 2019) - Cheng, X.X.; Ke, S.T.; Li, P.F.; Ge, Y.J.; Zhao, L.
Highlights: Sadek-Simiu method is proved to be applicable to non-Gaussian wind pressure samples. Influence of turbulence intensity on wind effects on cooling towers is revealed. Model test data are validated by full-scale measurement results. Accurate external extreme wind pressure distribution on cooling towers are formulated. Abstract: Current methods adopted by the Chinese Codes for calculating the external extreme wind pressure distribution on large cooling tower structures may result in an uneconomical structural design. Similar situation might hold true for other international standards, e.g., the German Code VGB-R 610Ue and the British Code BS4485. It is important therefore to accurately calculate the external extreme wind pressure distribution to ensure the suitable structural design of these large structures. However, two issues currently exist which hinder the calculation of accurate wind pressure distributions: (1) although wind pressure samples on tower surfaces are often found to be non-Gaussian features, limited peak factor calculation methods have been deemed to be applicable to non-Gaussian samples; and (2) the effects of free-stream turbulence on wind loads on large cooling towers are generally significant, which possibly further leads to a significant influence on the extreme wind pressure distributions obtained. In light of these issues, the applicability of the Sadek-Simiu method to non-Gaussian wind pressure samples is validated in this study and, based on quantifiable data, the limited influence of the turbulence intensity on the external extreme wind pressure distribution is also observed. With these findings, the external extreme wind pressure distribution on large cooling tower structures is calculated by averaging distributions around different horizontal sections obtained using the Sadek-Simiu method. Finally, the accuracy of the obtained external extreme wind pressure distribution is validated using full-scale measurement results. The obtained external extreme wind pressure distribution is formulated in this study which will facilitate the future improvements of the Chinese Codes and the German Code VGB-R 610Ue.